Combining Ability, Maternal Effects, and Heritability of Drought Tolerance, Yield and Yield Components in Sweetpotato - Rukundo, Placide; Shimelis, Hussein; Laing, Mark; Gahakwa, Daphrose (Frontiers in Plant Science, 2017)
Knowledge on gene action and trait expression are important for effective breeding. The objective of this study was to determine the general combining ability (GCA), specific combining ability (SCA), maternal effects and heritability of drought tolerance, yield and yield components of candidate sweetpotato clones. Twelve genotypes selected for their high yield, dry matter content or drought tolerance were crossed using a full diallel mating design. Families were field evaluated at Masoro, Karama and Rubona Research Stations of Rwanda Agriculture Board. Success rate of crosses varied from 1.8 to 62.5% with a mean of 18.8%. Family by site interaction had significant effect (P<0.01) on storage root and vine yields, total biomass and dry matter content of storage roots. The family effects were significant (P< 0.01) for all parameters measured. Broad sense heritability estimates were 0.95, 0.84, 0.68, 0.47, 0.74, 0.75, 0.50 and 0.58 for canopy temperature (CT), canopy wilting (CW), root yield, skin colour, flesh colour, dry matter content, vine yield and total biomass, respectively. The GCA effects of parents and SCA effects of crosses were significant (P<0.01) for CT, CW, storage root, vine and biomass yields, and dry matter content of storage root. The ratio of GCA/SCA effects for CT, CW, yield of storage roots and dry matter content of storage roots were higher than 50%, suggesting the preponderance of additive over non-additive gene action in the expression of these traits. Maternal effects were significant (P<0.05) among families for CT, CW, flesh color and dry matter content, vine yield and total biomass. Across sites, the best five selected families with significant SCA effects for storage root yield were, Nsasagatebo x Otada 24, Otada 24 x Ukerewe, 4-160 x Nsasagatebo, K513261 x 2005-034 and Ukerewe x K513261 with 11.0, 9.7, 9.3, 9.2, 8.6 t/ha, respectively. The selected families are valuable genetic resources for sweetpotato breeding for drought tolerance, yield and yield components in Rwanda or similar environments.